(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
he main goal of the present paper is to study the military strategies drawn up by the insurgents and the royalists in the Congregación de Dolores between 1810 and 1821. Between 1813 and 1814, the rebels organized military forces in Dolores with the aim of controlling mining in Guanajuato and thereby tried to dominate the towns and villages of the bajío. Ater 1814, this population had the highest importance in the attempt to attack the southern part of the intendency of San Luis Potosí and the so-called “barn of the New Spain”. Ater 1816, the royalist governments established the so-called “General Northern Headquarters of the Guanajuato Province”, with its seat in Dolores, whose principal military goal was to bring complete peace to this part of the New Spain.